Rancang Bangun Aplikasi Pengolahan Data Barang Inventaris Berbasis Mobile di Bidang Pemuda dan Olahraga - Alda, Muhamad; Ira Murni; Bagus Rizki Lubis; MHD Aria Agung Widodo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Inventory processing is an item data management activity carried out through a shopping budget or donations. This application is designed to provide easy access and speed in recording, managing and monitoring inventory in real-time. The aim of this research is to produce an Inventory Application at the Sergai Youth and Sports Office which can be used to process inventory data to make it more effective and accurate. This research uses data collection methods, namely interviews and literature studies, and for application development methods using the waterfall method. The results of this research obtained a system that is useful for processing inventory item data that will be used at the Youth and Sports Sector Office of DISPORAPARBUD SERGAI.